AI in Combating Cyber Threats to Indian Pharmaceutical Intellectual Property: Legal Perspectives - Gunjan Sharma; Anil G. Variath; Pushpa Medhoo; Abhishek Srivastava; Sneha Rathore; Damyanti Rathore (Journal of Pharmacy and Bioallied Sciences, 2025)
The decriminalization of homosexuality in India has been a long and complex legal battle, culminating in the landmark Supreme Court ruling in Navtej Singh Johar v. Union of India (2018), which struck down Section 377 of the Indian Penal Code. This research paper critically examines the evolution of legal and judicial perspectives on homosexuality in India, tracing key cases from Naz Foundation v. Government of National Capital Territory (NCT) of Delhi (2009) to Supriyo v. Union of India (2023). The paper explores the socio-legal implications of decriminalization, including its impact on lesbian, gay, bisexual, transgender, queer (LGBTQ+) rights, societal attitudes, and future legislative reforms. It also discusses the limitations of the ruling, particularly the absence of legal recognition of same-sex marriages and anti-discrimination protections. Drawing from legal precedents, human rights principles, and comparative law analysis, this study assesses whether the Indian legal system has adequately addressed the rights of the LGBTQ+ community. The findings suggest that while decriminalization was a crucial step toward equality, further reforms are necessary to ensure full legal and social inclusion. The paper concludes with recommendations for strengthening LGBTQ+ rights in India through policy changes, legal protections, and public awareness initiatives.